Prenatal diagnosis of campomelic dysplasia - Tongsong T. (2014)
A pregnant woman of 24 weeks' gestation underwent ultrasound examination for fetal anomaly screening. The ultrasound findings revealed a single fetus with biparietal diameter of 61 mm, which was consistent with menstrual dates. The thoracic cage was small compared to the abdomen with hypoplastic scapulae and normally ossified unfractured ribs. All bony structures demonstrated normal echogenicity. The upper long bones were normal length and shape. Both femurs and tibiae were obviously bowed anteriorly, and slightly shortened. Bilateral talipes equinovarus were clearly demonstrated. A prenatal diagnosis of campomelic dysplasia was made and was confirmed by postnatal radiography and autopsy. The sonographic diagnosis in this case was based on the findings of small thorax, hypoplastic scapulae and bowed tibiae and femurs.